A Case of Primary Ciliary Dyskinesia Caused by a Mutation in OFD1, Which Was Diagnosed Owing to Clostridium difficile Infection - Rina Hasegawa; Shinji Suzuki; Shigeo Nishimata; Yasuyo Kashiwagi; Natsuko Inagaki; Hisashi Kawashima (Pediatric Reports, 2021)
We report a Japanese 5-year-old boy with primary ciliary dyskinesia (PCD) which was diagnosed owing to Clostridium difficile (CD) infection caused by prolonged antibiotic exposure. He had intractable otitis media with effusion (OME) and had abdominal pain and diarrhea for 4 months after starting antibiotics administration. His stool contained CD toxin. After vancomycin treatment, his symptoms improved and his stools did not contain CD toxin. His past medical history included frequent pneumonia. We, therefore, performed electron microscopy of the biopsy specimen from his nasal mucosa and genetic testing, and he was diagnosed with PCD. PCD is a rare inherited genetic disease causing ciliary dysfunction, which is very difficult to diagnose because some children without PCD also develop the same symptoms. Therefore, children who have intractable OME, rhinosinusitis, frequent pneumonia, or bronchitis and are taking antibiotics for long periods of time should be checked for underlying diseases, such as PCD.